Optimizing Pulmonary Rehabilitation in Chronic Obstructive Pulmonary Disease – Practical Issues: A Canadian Thoracic Society Clinical Practice Guideline. Issue 4 (2010) - Marciniuk, Darcy D; Brooks, Dina; Butcher, Scott; Debigare, Richard; Dechman, Gail; Ford, Gordon; Pepin, Veronique; Reid, Darlene; Sheel, Andrew W; Stickland, Micheal K; Todd, David C; Walker, Shannon L; et al.
Abstract : Pulmonary rehabilitation (PR) participation is the standard of care for patients with chronic obstructive pulmonary disease (COPD) who remain symptomatic despite bronchodilator therapies. However, there are questions about specific aspects of PR programming including optimal site of rehabilitation delivery, components of rehabilitation programming, duration of rehabilitation, target populations and timing of rehabilitation. The present document was compiled to specifically address these important clinical issues, using an evidence-based, systematic review process led by a representative interprofessional panel of experts. The evidence reveals there are no differences in major patient-related outcomes of PR between nonhospital- (community or home sites) or hospital-based sites. There is strong support to recommend that COPD patients initiate PR within one month following an acute exacerbation due to benefits of improved dyspnea, exercise tolerance and health-related quality of life relative to usual care. Moreover, the benefits of PR are evident in both men and women, and in patients with moderate, severe and very severe COPD. The current review also suggests that longer PR programs, beyond six to eight weeks duration, be provided for COPD patients, and that while aerobic training is the foundation of PR, endurance and functional ability may be further improved with both aerobic and resistance training.